Prevalence and associated factors of non-variceal upper gastrointestinal bleeding among cirrhotic patients with upper gastrointestinal bleeding on follow-up at a Tertiary Hospital in Ethiopia - Mahlet Mitiku Desalegn; Henok Fisseha; Makida Girma Altaye; Kaleb Assefa Berhane; Wasihun Zerfu Zewde (PLoS ONE, 2026)
Background Liver cirrhosis is a major cause of morbidity and mortality worldwide. Non-variceal upper gastrointestinal bleeding (NVUIGB) accounts for 24–42% of bleeding episodes in cirrhotic patients and carries a mortality rate of 15–30%. Understanding its prevalence and associated factors is critical for prevention and improved outcomes. This study assessed the prevalence and predictors of NVUGIB among cirrhotic patients with upper gastrointestinal bleeding at a tertiary hospital in Addis Ababa, Ethiopia. Methods A hospital based cross-sectional study was conducted from December 2020 to December 2023. A total of 234 patients were included in the study. The collected data were analyzed using Statistical Package for Social Sciences (SPSS) version 26.0. Bivariable and multivariable logistic regression was used to assess association between dependent and independent variables. Adjusted odds ratio with a 95% confidence interval was used to estimate the strength of association and level of statistical significance was declared at p value <0.05. Results The prevalence of non-variceal upper gastrointestinal bleeding was 31.6% (95% CI: 26.0–37.8). with a mean (±SD) age of 39 ± 14 years. Independent predictors of non-variceal upper gastrointestinal bleeding included longer duration of cirrhosis (AOR = 1.01, 95% CI: 1.001–1.019, p = 0.03) and Human Immunodeficiency Virus (HIV) (AOR = 51.72, 95% CI: 5.65–471.8, p < 0.001). Lower odds of non-variceal upper gastrointestinal bleeding were observed in older patients (AOR = 0.96, 95% CI: 0.93–0.99, p = 0.007), those with hepatitis C virus (AOR = 0.12, 95% CI: 0.05–0.66, p = 0.009) or schistosomiasis (AOR = 0.03, 95% CI: 0.006–0.19, p < 0.001) as the cause of cirrhosis, prior beta-blocker use (AOR = 0.32, 95% CI: 0.14–0.70, p = 0.005), and higher international normalized ratio (AOR = 0.57, 95% CI: 0.36–0.89, p = 0.014). Non-variceal upper gastrointestinal bleeding patients also had lower systolic blood pressure at presentation (AOR = 0.97, 95% CI: 0.95–0.99, p = 0.010) but required fewer blood product transfusions (AOR = 0.25, 95% CI: 0.08–0.71, p = 0.009). Conclusion Non-variceal upper gastrointestinal bleeding accounted for nearly one-third (31.6%) of bleeding cases among cirrhosis patients with upper gastrointestinal bleeding. It was significantly associated with longer duration of cirrhosis, younger age, and the presence of comorbidities such as HIV. Targeted screening and preventive measures for high-risk patients may reduce the burden of NVUGIB.